Somatostatin receptors 3 and 5 potentiate cholinergic-nerve-mediated contraction in human bronchus - Brollo, Marion; Grassin-Delyle, Stanislas; Roquencourt, Camille; Longchampt, Elisabeth; Miguet-Besson, Isabelle; Glorion, Matthieu; Salvator, Hélène; Devillier, Philippe (Frontiers in Pharmacology, 2025)
AimThe role of somatostatin (SST) in the modulation of cholinergic neurotransmission has not been explored previously in human bronchi. We investigated the effects of SST, selective agonists of the five SST receptors SSTR, and octreotide (a SSTR2,3,5 agonist) on the cholinergic contraction induced in vitro either by acetylcholine or by electrical field stimulation (EFS) in human bronchial rings.MethodsHuman bronchial rings (n = 326) were obtained from 32 patients undergoing surgery for lung carcinoma. 5 Hz EFS (biphasic pulse width: 1 ms; constant current: 320 mA for 10 s) induced contractions that reached about ∼30% of the maximum contraction caused by 40 Hz EFS. Bronchial rings were stimulated for 240 min in the presence or absence of various concentrations of SST, octreotide, and selective agonists of each of the five SSTR receptors. Furthermore, the tissue and cellular locations of each of the five types of SSTR was determined by immunohistochemistry.ResultsSST, octreotide, and the SSTR agonists did not change the resting tone or the contractions produced by the cumulative addition of acetylcholine (10−9 to 10−3 M). In contrast, octreotide and the SSTR3 and SSTR5 agonists significantly increased the EFS-induced contractions. Immunoreactivity for all SSTR subtypes was detected in the airway’s neural ganglia.ConclusionThe present study provided new data on the location of SSTR in the human lung: notably, all types of receptor were found in the parasympathetic nerve ganglia of the bronchial wall. We suggest that the activation of prejunctional SSTR3 and SSTR5 receptors potentiates cholinergic-nerve-mediated contraction induced by EFS in human bronchi.